Epic ebook Legends of fantasy. - Adams, John Joseph (2012)
There is a sickness in the land. Prophets tell of the fall of empires, the rise of champions. Great beasts stir in vaults beneath the hills, beneath the waves. Armies mass. Gods walk. The world will be torn asunder. Epic fantasy is storytelling at its biggest and best. From the creation myths and quest sagas of ancient times to the mega-popular fantasy novels of today, these are the stories that express our greatest hopes and fears, that create worlds so rich we long to return to them again and again, and that inspire us with their timeless values of courage and friendship in the face of ultimate evil—tales that transport us to the most ancient realms and show us the most noble sacrifices, the most astonishing wonders. Now acclaimed editor John Joseph Adams ( Wastelands , The Living Dead ) brings you seventeen tales by today's leading authors of epic fantasy, including George R. R. Martin (A Song of Ice and Fire), Ursula K. Le Guin (Earthsea), Robin Hobb (Realms of Elderlings), Kate Elliott (Crown of Stars), Tad Williams (Of Memory, Sorrow & Thorn), Patrick Rothfuss (The Kingkiller Chronicle), and more. Return again to lands you've loved or visit magical new worlds. Victory against the coming darkness is never certain, but one thing's for sure—your adventure will be epic.